Investigation of automatic frequency and power control system modes with regulatory generators - Dryomin I.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2011)
Solution of regulation problems in the traditional automatic frequency and power control system (AFPC) lies in the input/output replacement capacity – regulatory generators. Techno-economic indicators of AFPC quality depend on the parameters and type of the law of control. Investigation of the law of control, based on appropriate mathematical models, will identify the most effective of these laws in accordance with the selected quality indicators.Numerical simulation was done on the basis of the mathematical model of Ukraine power system. Investigation of main laws of control (proportional, proportional-differential (PD) and proportional-integral-differential (PID)) was realized by numerical simulation. The investigation was done by comparing the characteristics of the simulated power system values (system frequency, generator capacity, load capacity and regulatory generator capacity), under actions of the various laws in the power system with perturbation (emergency shutoff of generating capacity).As the result of the investigation was found that the use of proportional law is impractical due to the oscillatory nature of the transient process, its staticism and duration. The main disadvantage of PD-law is in the existence of staticism. Action of PID-law satisfies the requirements ENTSO-E, but its implementation requires regulatory generators with small inertia constant.